Renovando a tradição: o caso da Cavalhada Mirim na comunidade de Morro Vermelho - Camila Pereira Lisboa (2014)
Our journey goes toward Morro Vermelho, rural district of Caeté, near Belo Horizonte (MG). There we found residents proud to preserve their traditions, some of them dating back to more than three centuries. While some traditions remained, others were lost and others were created, such as the Cavalhada Mirim, who was born in the eighties of the 20th century. Initially, it was proposed as a way to create a space for the children, who were playing to imitate knights from Cavalhada of Our Lady of Nazareth, the oldest tradition of Morro Vermelho. But the years have passed and still the Cavalhada Mirim keeps happening, especially due to commitment of three generations of responsible for rehearsing the boys and take care of all the details of the celebration. Then, our goal was to investigate how this responsibility was, and still is, lived by these individuals from different generations, seeking to know the motivations for creating the party, keep it and pass it on to others who could ensure their existence. In order to assist us in the understanding of tradition, culture and other dear concepts to our work, we rely on the help of authors from different areas of knowledge, always in view of the connection between subjectivity and context - foundation of Social Psychology. Our main theoretical and methodological referential was classical phenomenology, where the concept of life-world has a lot to say about the world of traditions. Moreover, we resorted to ideas of Maurice Halbwachs, from the realization that the past is dynamic and remains very much alive in the present. We undertook a qualitative and ethnographic research, observing, photographing and collecting stories that could help us to understand the topic in question. We analyzed the interviews of the three responsible for Cavalhada Mirim, one from each generation. We tried made a rigorous analysis, as proposed by Husserl and systematized by van der Leeuw. The most significant livings of each participant about the responsibility for Cavalhada Mirim were then placed into categories, after used to describe these livings transversely in these three generations. Then, we could observe a legitimizing of the children in the traditional festivals of Morro Vermelho. Additionally, we also noticed a significant relationship with the figure of Our Lady. This religious experience born from an influence of family and community, originating different ways of response - among them, the responsibility. We noticed too that each subject incorporate a moment by this life course from Morro Vermelho: by initiation in devotion and traditions, to answer as responsibility, culminating in the concern of transmission to subsequent generations. We note that the responsibility is not supported as a mere obligation, but as a desire to keep something truly significant for these three subjects in particular and to Morro Vermelho in general, helping to sustain local traditions.